2009
DOI: 10.1002/adfm.200900932
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Structural Characterizations of Individual Single‐, Double‐, and Multi‐Walled Carbon Nanotubes

Abstract: Thermal conductance measurements of individual single‐ (S), double‐ (D), and multi‐ (M) walled (W) carbon nanotubes (CNTs) grown using thermal chemical vapor deposition between two suspended microthermometers are reported. The crystal structure of the measured CNT samples is characterized in detail using transmission electron microscopy (TEM). The thermal conductance, diameter, and chirality are all determined on the same individual SWCNT. The thermal contact resistance per unit length is obtained as 78–585 m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
133
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(140 citation statements)
references
References 52 publications
(84 reference statements)
4
133
1
2
Order By: Relevance
“…2,[5][6][7][8][9][10][11][12] This incongruity in some cases can be attributed to variations in thermal contact resistance R c , 13 a parameter that has recently received much attention, with studies on the subject reporting values that vary widely. 13,[14][15][16][17][18][19][20][21][22] For example, Maune et al perform thermometry employing electrical breakdown of CNTs to report R c values of 0.6--3.0 K·m/W, 15 whereas Tsen et al…”
mentioning
confidence: 99%
“…2,[5][6][7][8][9][10][11][12] This incongruity in some cases can be attributed to variations in thermal contact resistance R c , 13 a parameter that has recently received much attention, with studies on the subject reporting values that vary widely. 13,[14][15][16][17][18][19][20][21][22] For example, Maune et al perform thermometry employing electrical breakdown of CNTs to report R c values of 0.6--3.0 K·m/W, 15 whereas Tsen et al…”
mentioning
confidence: 99%
“…Although these values are much smaller than the actual suspended lengths and widths of these samples, a low interface transmission coefficient between the supported and suspended graphene segments can reduce the effective boundary length to α λ L, as illustrated in Equation (4). In addition, the calculation result becomes higher than the measurement data at temperatures above 250 K for the bi-layer graphene sample of Pettes et al 30 However, the discrepancy can still be attributed to either a frequency-dependent α, which is lower for the higher frequency phonons, 12 or additional point defect scattering, which is also more pronounced for the higher frequency phonons populated at higher temperatures. In particular, among the three samples examined here, only this bi-layer sample was exposed to electron beam irradiation during the sample preparation process.…”
Section: Thermal Conductivitymentioning
confidence: 42%
“…The interface heat transfer between the supported graphene segment and the support results in a hyperbolic temperature distribution in the supported graphene segment, similar to that found along a fin with the base connected to a heat source and the circumference surface exposed to a reservoir at a different temperature. 28 Hence, a fin resistance model has been developed in prior works for the calculation of the sample-support interface thermal resistance as [29][30][31][32] …”
Section: -6mentioning
confidence: 99%
“…Owning to these advanced properties as well as abundance of carbon on the earth, CNT is an important candidate to build flexible electronics. [25][26][27] However, it is seldom regarded as a TE material due to its poor Seebeck coefficient (< 60 μV/K) 28 and high thermal conductivity of a single tube (~ 250-10000 Wm -1 K -1 for single tube or aligned arrays) [29][30][31] . It has been reported that low thermal conductivities can be obtained in CNTs/conductive polymer composites and processed tubes.…”
Section: Introductionmentioning
confidence: 99%